Construindo histórias, desafiando barreiras: trajetórias laborais de mulheres negras em uma perspectiva intergeracional sob a ótica interseccional - Pereira, Lourrayne Dias (2024)
In Brazilian society, as well as in the labor market, racial inequality has been structurally present since the beginning of time, and over the years, it has become increasingly necessary to discuss the topic. Thus, this study sought to analyze the work paths of black women, considering the intersectional markers of gender, race, and class, as well as the influence of generations throughout their professional trajectories. This is a qualitative research approach, and the method used was life trajectories, with a labor thematic focus. Data collection was carried out through in-depth interviews with the aim of developing a thematic and structural analysis, with the participation of a group of three black women. The general objective of this study is to analyze the work trajectories of black women from an intergenerational perspective, from the perspective of intersectionality. Through the specific objectives, we intend to describe the work trajectories of black women, observe how class, gender, and race influence these trajectories, and finally, analyze how intergenerationality permeates these trajectories. Based on the arguments presented, this study sought to answer the research question: How are the professional trajectories of black women constructed from an intergenerational and intersectional perspective? Issues related to their professional realities, their perceptions, and the greatest challenges they face were addressed, and the results show that these trajectories are marked by structural inequalities of gender, race, and class, but also by resistance and resignification. The study reinforces the urgency of public policies that expand opportunities and value their potential. It is concluded that the trajectories reflect a continuous confrontation of inequalities and a source of social transformation.